2020
DOI: 10.2147/copd.s234042
|View full text |Cite
|
Sign up to set email alerts
|

<p>Geographical Disparity and Associated Factors of COPD Prevalence in China: A Spatial Analysis of National Cross-Sectional Study</p>

Abstract: Purpose: COPD prevalence has rapidly increased in China, but the geographical disparities in COPD prevalence remain largely unknown. This study aimed to assess city-level disparities in COPD prevalence and identify the relative importance of COPD related risk factors in mainland China. Patients and Methods: A nationwide cross-sectional study of COPD recruited 66,752 adults across the mainland China between 2014 and 2015. Patients with COPD were ascertained by a post-bronchodilator pulmonary function test. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Further investigations are, therefore, needed to clarify the roles of these factors in predicting OSA. Furthermore, a better understanding of the important risk factors and clinical outcomes of patients with overlap syndrome in different geographical areas would help the relevant health authorities to implement targeted intervention strategies [ 17 ]. We conducted a cross-sectional community-based study in China to clarify the prevalence, clinical characteristics, risk factors of COPD with OSA, and the relationship between airflow limitation in COPD and severity of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Further investigations are, therefore, needed to clarify the roles of these factors in predicting OSA. Furthermore, a better understanding of the important risk factors and clinical outcomes of patients with overlap syndrome in different geographical areas would help the relevant health authorities to implement targeted intervention strategies [ 17 ]. We conducted a cross-sectional community-based study in China to clarify the prevalence, clinical characteristics, risk factors of COPD with OSA, and the relationship between airflow limitation in COPD and severity of OSA.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients in our study were male, which is consistent with previous studies. Nationwide crosssectional studies in China have demonstrated a higher prevalence of COPD among males [21,27], while the prevalence is more similar between the sexes in Europe and the US [28]. These data further demonstrate that the population in the REAL study is nationally representative.…”
Section: Discussionmentioning
confidence: 53%
“…Geographical differences in COPD incidence, mortality, and prevalence have been reported in other countries [16][17][18][19][20][21], and factors associated with these regional differences have been identified. A study in Taiwan has reported that factors such as smoking prevalence, percentage of aborigines, and concentration of particulate matter 10 are positively associated with regional COPD mortality rate [20], and another study in China has showed that smoking and exposure to particulate matter 2.5 are positively associated with COPD prevalence [18]. Another study that investigated factors associated with COPD mortality in Shanghai has revealed that extremely low temperatures in the month before death, shorter distances to the highway, and lower gross domestic product are associated with mortality [21].…”
Section: Introductionmentioning
confidence: 83%